Structural and biochemical characterization of NS2BCF48-NS3fl from flaviviruses - Teo, Fyn Chwee Fang (Nanyang Technological University, 2024)
Dengue virus (DENV) is an emerging and re-emerging mosquito-borne virus of significant public health concern. The DENV has a single-stranded RNA genome that is translated into a polyprotein and then cleaved into individual viral proteins by the host and viral proteases. Non-structural (NS) protein-3 is a multi-functional enzyme that has an N-terminal protease and C-terminal helicase and requires a co-factor, NS2B, for folding and enzymatic activity. NS2B-NS3 is crucial in viral replication and assembly, making it a promising candidate for antiviral drug design. Our study employed crosslinking mass spectrometry in conjunction with biochemical assays to characterize the dynamic interactions between NS2B S48 and NS3 helicase domain within NS2BCF48NS3fl of DEN1-3. A comparison of our findings from DENV1-4 against previously studied DENV4 NS2BCF48NS3pro reveals the crosslink interactions between NS2B S48 and NS3 to be highly conserved across flaviviruses, giving rise to a promising allosteric target for antiviral design. The mapping of NS2B S48 with NS3 full-length exhibited violated inter-crosslink interactions indicating there is an alternative conformation(s) that is/are not observed in the current crystal structure. This study has enhanced our comprehension of the dynamic behaviors of NS2BCF48NS3fl.